Sosialisasi Pengelolaan Sampah Untuk Kebersihan Lingkungan Pasar di Kecataman Lembah Melintang dalam Upaya Memberdayakan Masyarakat - Fitria Fricilia, Frisca (Pustaka : Jurnal Ilmu-Ilmu Budaya; Vol 22 No 2 (2022)DO - 10.24843/PJIIB.2022.v22.i02.p04, 2022)
Garbage is now everywhere. Either in a residential area or in the center of the economy. In the economic environment, one of which is the market as an area that generally produces a lot of waste. Therefore, this paper aims to provide education and instill the value of the impact caused and how management can need to be carried out regarding the waste left by traders in the Ujung Gading market, Lembah Lintas District so that the community has power in the waste management process. This study uses a literature review, which is to collect information and data from a literature review